Readings in Formal Epistemology - Arló-Costa, Horacio; Hendricks, Vincent F.; Benthem, Johan van (Springer, 2016)
“Formal epistemology” is a term coined in the late 1990s for a new constellation of interests in philosophy, merging traditional epistemological concerns with new influences from surrounding disciplines like linguistics, game theory, and computer science. Of course, this movement did not spring to life just then. Formal epistemological studies may be found in the classic works of Carnap, Hintikka, Levi, Lewis, Kripke, Putnam, Quine, and many others. Formal epistemology addresses a growing agenda of problems concerning knowledge, belief, certainty, rationality, deliberation, decision, strategy, action, and agent interaction – and it does so using methods from logic, probability theory, computability theory, decision theory, game theory, and elsewhere. The use of these formal tools is to rigorously formulate, analyze, and sometimes solve important issues of interest to philosophers but also to researchers in other disciplines, from the natural sciences and humanities to the social and cognitive sciences and sometimes even the realm of technology. This makes formal epistemology an interdisciplinary endeavor practiced by philosophers, logicians, mathematicians, computer scientists, theoretical economists, social scientists, cognitive psychologists, etc. Although a relative newcomer, formal epistemology is already establishing itself in research environments and university curricula. There are conferences, workshops, centers, and jobs in formal epistemology, and several institutions offer courses or seminars in the field. Yet no volume is in existence comprising canonical texts that define the field by exemplars. Lecturers and students are forced to collect influential classics and seminal contemporary papers from uneven sources, some of them hard to obtain even for university libraries. There are excellent anthologies in mainstream epistemology, but these are not tuned to new fruitful interactions between the mainstream and a wider spectrum of formal approaches.